Methanol induced intracranial hemorrhage: A rare case report - Twinkle, Furial Quraishi; Rahman, Aminur; Giasuddin, Rubayat Sheik; Hakim, Khondker Mahmudul; Shapnil, Ahammed Ali; Rahman, Md Hamimur; Akash, Meherul Alam; Quraishi, Firoz Ahmed (Bangladesh Journal of Medicine, 2022)
Intracranial hemorrhage is a rare but fatal complication in methanol poisoning. We report a case of large bilateral basal ganglia hematoma in a 29-years old man with methanol poisoning. He drank alcohol, and was admitted to a tertiary level hospital 6 hours post-ingestion for depressed mental status, lower blood pressure, and high anion gap metabolic acidosis. After fourteen days of methanol exposure, he suddenly developed left sided weakness with one episode of seizure attack. MRI of brain was carried out and showed large intracerebral bleed basal ganglia, specially putaminal and brain edema with midline shift. The uncommon presentation of methanol poisoning is highlighted in this case report. Bangladesh J Medicine 2022; 33: 300-303